1988
DOI: 10.1107/s0021889887010409
|View full text |Cite
|
Sign up to set email alerts
|

On the Porod law

Abstract: The Porod law states that i(h), the intensity of Xradiation scattered by an ideal multiphase noncrystalline system, for 'large' momentum transfer values (= h) approaches C~h-4 and that ~ is linearly related to the interphase surface areas. A more general expression is obtained which relates the value of the correlation-function derivative at the origin to the integral of the discontinuity of the electron density fluctuation along the discontinuity surface. Debye's assumption, by which the continuous electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 22 publications
4
63
0
Order By: Relevance
“…However, even in Ruland's (1987) most recent analysis devoted to the case of fluctuating interfaces, the discussion has been confined to the Porod contribution. Ruland's procedure will be briefly reviewed now and slightly reformulated by using some considerations reported by Ciccariello et al (1988). In general, a sample's electron-density fluctuation can be written as r/(r) = r/o(r ) + vo(r ).…”
Section: Smoothing Functionsmentioning
confidence: 99%
“…However, even in Ruland's (1987) most recent analysis devoted to the case of fluctuating interfaces, the discussion has been confined to the Porod contribution. Ruland's procedure will be briefly reviewed now and slightly reformulated by using some considerations reported by Ciccariello et al (1988). In general, a sample's electron-density fluctuation can be written as r/(r) = r/o(r ) + vo(r ).…”
Section: Smoothing Functionsmentioning
confidence: 99%
“…Thus, the dominating correction to the first order scaling p∝φ 3 is logarithmic, following from the logarithmic rescaling of bending rigidity and saddle-splay modulus. We have also demonstrated that the simulations reproduce the Porod laws for bulk 12,52 and film 53 scattering qualitatively. Finally, we have shown that the low-q behavior of the scattering intensity in film scattering matches theoretical predictions of a q −1 behavior.…”
Section: Discussionmentioning
confidence: 67%
“…In a strict sense, the observation of a Porod plateau depends on the existence of sharp discontinuities in the electronic density from one phase to another. In other respects, Ciccariello, Goodisman & Brumberger (1988)-henceforth referred to as CGB -showed that Porod's law can only be verified, strictly speaking, over a confined domain when a real system is dealt with. As a result, it is possible to observe more than one plateau in a SAS curve.…”
Section: Introductionmentioning
confidence: 99%